ENGLISH LEARNING AT A DISTANCE: A CASE STUDY ON SOCIAL-LINGUISTIC AND DIGITAL INCLUSION - Simone Tiemi Hashiguti; Cristiane C. de Paula Brito (European Scientific Journal, ESJ, 2015)
Considering that there is a political-digital movement of globalization of which Brazil makes part and for which access to English knowledge is demanded, this paper discusses the theme of social/digital inclusion as an effect of a formal education in English at university level in Brazil. With the understanding that digital and social inclusions can be facets of one same process, a third, linguistic facet, is incorporated in our reflection and made visible, as the three aspects are conceived as interconstitutive of an event that can be, for certain postcolonial, non English speaking countries, of the rising of a social visibility and place. The corpus of analysis chosen for this study is hybrid, composed of a collection of answers to questionnaires and postings in discussion forums by students who participate in a four-year undergraduate long distance course of English and English Literature provided by a Federal University in the Southeast region of Brazil. The course licenses teachers for K-12 schools and is part of a Federal Program do graduate teachers. Our theoretical framework is a discursive one (Pêcheux, 1969, 1975), from which we see both English and ICTs as kinds of knowledge that are practiced within conditions of production related to history, processes of memory and subjectivation, together with post-colonial reflections on language policies and practices (Spivak, 1999), from which we discuss the specific characteristics of teaching/learning English in Brazil.